2021
DOI: 10.7554/elife.65394
|View full text |Cite
|
Sign up to set email alerts
|

The whale shark genome reveals patterns of vertebrate gene family evolution

Abstract: Chondrichthyes (cartilaginous fishes) are fundamental for understanding vertebrate evolution, yet their genomes are understudied. We report long-read sequencing of the whale shark genome to generate the best gapless chondrichthyan genome assembly yet with higher contig contiguity than all other cartilaginous fish genomes, and studied vertebrate genomic evolution of ancestral gene families, immunity, and gigantism. We found a major increase in gene families at the origin of gnathostomes (jawed vertebrates) inde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 162 publications
(306 reference statements)
3
23
0
Order By: Relevance
“…The same study has also shown high expression of these genes in immune tissues and their significant response to bacterial/viral ligands. The presence of NLRs has been predicted in chondrichthyes such as grey bamboo shark [34] , whale shark [35] and major ray-finned fishes like bichir, American paddlefish, alligator gar, spotted gar and bowfin [36] following in silico analysis. In teleosts, whole genome sequencing along with advanced bioinformatics tools has facilitated the identification of several NLR transcripts over the years ( Table 1 ) having similar domain architecture to mammals.…”
Section: Diversity Of Nlrsmentioning
confidence: 99%
“…The same study has also shown high expression of these genes in immune tissues and their significant response to bacterial/viral ligands. The presence of NLRs has been predicted in chondrichthyes such as grey bamboo shark [34] , whale shark [35] and major ray-finned fishes like bichir, American paddlefish, alligator gar, spotted gar and bowfin [36] following in silico analysis. In teleosts, whole genome sequencing along with advanced bioinformatics tools has facilitated the identification of several NLR transcripts over the years ( Table 1 ) having similar domain architecture to mammals.…”
Section: Diversity Of Nlrsmentioning
confidence: 99%
“…Transcriptome completeness was assessed using BUSCO v.3.0.2 ( 34 , 35 ) against the vertebrata Odb10 database. 83.5% complete orthologs were recovered ( Supplementary Table S4 ), comparing favourably to the most recent whale shark genome assembly ( 56 ), which showed a completeness of 78.7% using the same approach. This confirmed that our new transcriptome is an appropriate reference database for high-throughput proteomics in nurse shark, while further representing a useful resource available for future investigations.…”
Section: Resultsmentioning
confidence: 65%
“…Consequently, plasma proteomics offers a useful approach to inform on immunological functions. To date, very little is known about the plasma proteins of cartilaginous fishes or their individual contribution to immune defence, with studies primarily addressing their identification and evolution at the genomic level rather than their presence in plasma and associated immune responsiveness (e.g., 22 24 ). Where functional studies have been performed, these have focused on Igs (e.g., 4 , 25 ) or individual proteins that are present at high abundance in shark plasma, e.g., haptoglobin and hemopexin ( 6 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being first described as a member of the TLR1 family ( 8 ), some authors have since proposed that TLR15 should be considered as a separate family. Indeed, TLR15 appears to have evolved independently from other TLR1 subfamily members ( 18 , 20 ), and shows structural differences such as an intact asparagine ladder and an ectodomain with single-domain architecture, instead of the three-domain architecture shared by all TLR1 family members ( 3 , 6 ).…”
Section: Introductionmentioning
confidence: 99%